De-Moivre and Euler Formulae for Dual-Complex Numbers - Mehmet Ali Güngör; Ömer Tetik (Universal Journal of Mathematics and Applications, 2019)
In this study, we generalize the well-known formulae of De-Moivre and Euler of complex numbers to dual-complex numbers. Furthermore, we investigate the roots and powers of a dual-complex number by using these formulae. Consequently, we give some examples to illustrate the main results in this paper.